2021
DOI: 10.5430/ijfr.v12n2p1
|View full text |Cite
|
Sign up to set email alerts
|

Financial Risk Tolerance: The Case of Older Chinese in Klang Valley, Malaysia 2020

Abstract: Ageing demographic profiles pose challenges to the nation as policymakers are concerned about the health, public pension and the financial management of the society. In Malaysia, retirees are mostly dependent on savings from the Employees Provident Fund (EPF), a government agency that manages savings and retirement plans for private-sector employees and non-pensionable public servants. Many Malaysians aged past the targeted retirement age of 60 years old chose to remain in the workforce, mainly due to insuffic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 24 publications
1
8
1
Order By: Relevance
“…As seen in Figure 1 below, elderly financial satisfaction does not significantly affect their financial risk tolerance; the first hypothesis (H1) is not supported (FS-RT: 0.044 and p-value more than 5% level). This finding differs from previous studies, such as Chong et al (2021) focused on the Malaysian Chinese in Klang Valley and discovered that financial satisfaction and risk tolerance are positively related. Besides, Rajesh (2018) on Indian households' financial literacy also encountered a negative relationship between economic satisfaction and risk tolerance.…”
Section: Resultscontrasting
confidence: 99%
See 4 more Smart Citations
“…As seen in Figure 1 below, elderly financial satisfaction does not significantly affect their financial risk tolerance; the first hypothesis (H1) is not supported (FS-RT: 0.044 and p-value more than 5% level). This finding differs from previous studies, such as Chong et al (2021) focused on the Malaysian Chinese in Klang Valley and discovered that financial satisfaction and risk tolerance are positively related. Besides, Rajesh (2018) on Indian households' financial literacy also encountered a negative relationship between economic satisfaction and risk tolerance.…”
Section: Resultscontrasting
confidence: 99%
“…As mentioned earlier, in hypothesis 1, financial satisfaction has no significant direct association with financial risk tolerance.This study adopts Process macro for SPSS version 4.0 and Model 4 (mediation analysis) to analyse the direct and indirect effects (mediated by the TPB) between financial satisfaction and financial risk tolerance among Malaysian elderly in Klang Valley, Malaysia. This paper extends the previous literature ofChong et al (2021) by including Malaysian elderly of Chinese, Malay and Indian ethnicity. The results from this study have revealed that financial satisfaction does not significantly influence the elderly financial risk tolerance, which is inconsistent with the previous studies conducted before…”
supporting
confidence: 54%
See 3 more Smart Citations